Transcranial magnetic stimulation (TMS)-induced Blindsight of Orientation is Degraded Conscious Vision - Koivisto Mika; Leino Kalle; Pekkarinen Aino; Karttunen Jaakko; Railo Henry; Hurme Mikko (Elsevier, 2022)
Patients with blindsight are blind due to an early visual cortical lesion, but they can discriminate stimuli presented to the blind visual field better than chance. Studies using transcranial magnetic stimulation (TMS) of early visual cortex have tried to induce blindsight-like behaviour in neurologically healthy individuals, but the studies have yielded varied results. We hypothesized that previous demonstrations of TMS-induced blindsight may result from degraded awareness of the stimuli due to the use of dichotomous visibility scales in measuring awareness. In the present study, TMS was applied to early visual cortex during an orientation discrimination task and the subjective scale measuring awareness was manipulated: The participants reported their conscious perception either using a dichotomous scale or a 4-point Perceptual Awareness Scale. Although the results with the dichotomous scale replicated previous reports of blindsight-like behaviour, there was no evidence of TMSinduced blindsight for orientation when the participants used the lowest rating of the 4-point graded scale to indicate that they were not aware of the presence of the stimulus. Moreover, signal detection analyses indicated that across participants, the individual's sensitivity to consciously discriminate orientation predicted behaviour on reportedly unconscious trials. These results suggest that blindsight-like discrimination of orientation in neurologically healthy individuals does not occur for completely invisible stimuli, that is, when the observers do not report any kind of consciousness of the stimulus. TMS-induced blindsight for orientation is likely degraded conscious vision.
(c) 2021 The Author(s). Published by Elsevier Ltd on behalf of IBRO. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).